Law of King Canute A. D. 1016-1035. Secular Dooms, Cap. 80 - (:unkn) unknown (My University)
Allowed individuals to hunt on their own lands. Anyone caught hunting on the King's lands would suffer "the full penalty."
Keywords: HUNTING REGULATION